A freshwater analog for the production of Epiphyton‐like microfossils. Issue 5 (19th April 2019) - Ibarra, Yadira; Sanon, Sonicah
Abstract: Calcified microbial microfossils—often interpreted as cyanobacteria—were important components of Precambrian and Paleozoic limestones, but their paucity in modern marine environments complicates our ability to make conclusive interpretations about their taxonomic affinity and geologic significance. Freshwater spring‐associated limestones (e.g., travertine and tufa) serve as terrestrial analogs to investigate mineralization in and around aquatic biofilms on observable timescales. We document the diagenesis of calcite fabrics associated with the freshwater algae Oocardium stratum, an epiphytic colonial green algae (desmid) known for producing stalks of extracellular polymeric substances (EPS) and passively producing a bifurcating tubular calcite monocrystal. Bifurcating EPS stalks produced by Oocardium colonies can become calcified and preserved in ancient carbonate deposits. Calcified micritic EPS stalks have a filamentous morphology, show evidence of branching, and maintain uniformity in diameter thickness throughout the mm‐scale colony, much like the enigmatic calcimicrobe Epiphyton . We provide a mechanism by which calcification associated with a colonial semispherical micro‐organism produces microfossils that deceptively resemble filamentous forms. These findings have implications for the use of morphological traits when assigning taxonomic affinities to extinct microfossil groups and highlight the utility of calcifying freshwater modern environments to investigate microbial taphonomy.